Stripped: contribution of cyanobacterial extracellular polymeric substances to the adsorption of rare earth elements from aqueous solutions - Paper, Michael; Jung, Patrick; Koch, Max; Lakatos, Michael; Nilges, Tom; Brück, Thomas B. (Frontiers in Bioengineering and Biotechnology, 2023)
Currently, global societies are undergoing a transformation facilitated by green high technologies that are heavily depending on rare earth elements (REEs) such as cerium (Ce), neodymium (Nd), terbium (Tb), and lanthanum (La). The occurrence of productive mining sites e.g. is limited and production is often costly and environmentally harmful. As a consequence of increased utilization, REE enter our ecosystem as industrial process water or wastewater and become highly diluted. Once diluted, they can hardly be recovered by conventional techniques but using cyanobacterial biomass in a biosorptionbased process is a promising eco-friendly approach. Cyanobacteria can produce extracellular polymeric substances (EPS) that show high affinity to metal cations. However, the adsorption of REE by EPS has not been part of extensive research, thus we evaluated the role of EPS during biosorption of Ce, Nd, Tb, and La for three terrestrial, heterocytous cyanobacterial strains. We cultivated them under N-limited and non-limited conditions and extracted their EPS for compositional analyses. Subsequently, we investigated the metal uptake of a) the extracted EPS, b) the biomass freed from EPS and c) the intact biomass with EPS by comparing the amount of sorbed REEs. In comparison of freed to intact biomass 16% (Komarekiella sp. 89.12), 28% (Desmonostoc muscorum 90.03) to 41% (Nostoc sp. 20.02) of REE adsorption remain to the biosorption of the extracellular EPS. The glucoserich EPS (15-43 % relative concentration) of all three strains grown under nitrogen-limited conditions showed significantly higher biosorption rates for all REEs. We also found a significantly higher maximum adsorption capacity of all REEs for the extracted EPS compared to cells without EPS and untreated biomass, highlighting the important role of the EPS as a binding site for REEs during the biosorption process. Maximum adsorption capacities for the tested REEs of extracted EPS were 123.9-138.2 mg g-1 for Komarekiella sp. 89.12, 133.1-137.4 mg g-1 for Desmonostoc muscorum 90.03, This is a provisional file, not the final typeset article and 103.5-129.3 mg g-1 for Nostoc sp. 20.02. EPS from cyanobacteria could thus be used as efficient biosorbents in future applications for REE recycling, for example from industrial process water and wastewater streams.